Development of a two stage inspection process for the assessment of deteriorating infrastructure - O'CONNOR, ALAN (My University, 2010)
Inspection based maintenance strategies can provide an efficient tool for the management of ageing infrastructure subjected to deterioration. Many of these methods rely on quantitative data from inspections, rather than qualitative and subjective data. The focus of this paper is on the development of an inspection based decision scheme, incorporating analysis on the effect of the cost and quality of NDT tools to assess the condition of infrastructure elements/networks during their lifetime. For the first time the two aspects of an inspection are considered, i.e. detection and sizing. Since each stage of an inspection is carried out for a distinct purpose, different parameters are used to represent each procedure and both have been incorporated into a maintenance management model. The separation of these procedures allows the interaction between the two inspection techniques to be studied. The inspection for detection process acts as a screening exercise to determine which defects require further inspection for sizing. A decision tool is developed, which allows the owner/manager of the infrastructural element/network to choose the most cost efficient maintenance management plan based upon his/her specific requirements.
PUBLISHED
Keywords: nfrastructure; Markov deterioration; Inspection; Maintenance management; Repair